A generation divided : the new left, the new right, and the 1960s - Klatch, Rebecca E. (University of California Press, 1999)
The 1960s was not just an era of civil rights, anti-war protest women's liberation and rock festivals. This text examines the generation that came into political consciousness during the 1960s, telling the story of the New Right and New Left.